2017
DOI: 10.1182/blood-2016-10-695957
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, risk stratification, and response evaluation in classical myeloproliferative neoplasms

Abstract: Philadelphia-negative classical myeloproliferative neoplasms (MPNs) include polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). The 2016 revision of the WHO Classification of Tumours of Haematopoietic and Lymphoid Tissues includes new criteria for the diagnosis of these disorders. Somatic mutations in the 3 driver genes, that is, JAK2, CALR, and MPL, represent major diagnostic criteria in combination with hematologic and morphological abnormalities. PV is characterized by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
227
1
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(241 citation statements)
references
References 98 publications
4
227
1
9
Order By: Relevance
“…In recent years, investigation on MPNs revealed that there are three driver mutations (JAK2, MPL and CALR) essential as clonal markers, activating the cytokine receptor JAK2 signaling pathway and the downstream effectors (30,57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, investigation on MPNs revealed that there are three driver mutations (JAK2, MPL and CALR) essential as clonal markers, activating the cytokine receptor JAK2 signaling pathway and the downstream effectors (30,57).…”
Section: Discussionmentioning
confidence: 99%
“…Although JAK2 V617F homozygous subclones are present in PV and ET patients, the expansion of a dominant homozygous subclone occurs almost exclusively in PV patients (~80% in PV and 50% in ET) (33,57), due to either additional genetic or epigenetic events or non-cell-autonomous selective pressures, such as low levels of circulating erythropoietin in the context of elevated hematocrit (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CALRETICULIN ( CALR ) driver mutation was identified in approximately 73% of JAK2/MPL mutation-negative ET and MF patients [23]. Mutations occur in exon 9 of CALR in the majority of JAK2 wild-type MPN cases.…”
Section: Targets In Mpn and Driver Mutationsmentioning
confidence: 99%
“…Interestingly, and very reminiscent, STAT5 activation at the ER–Golgi was also described in Flt3-ITD + or KIT D816V + AML cases. Analysis of patient data suggests that CALR mutation-positive patients have a more favorable clinical outcome than patients with JAK2 or MPL mutation-positive MPNs due to a lower risk of thrombosis [23]. …”
Section: Targets In Mpn and Driver Mutationsmentioning
confidence: 99%